The Effect of Anti-browning Agent Activated Carbon and Polyvinyl Pyrrolidone on the Rooting of Embryo Seedlings of “FengDan” and Its Transcriptome Analysis - Chen, Xia; Yu, Chao; Nie, Jingtao; Yang, Hongmin; Ji, Wen; Xu, Gangwei; Zhu, Huijun; Jin, Songheng; Zhu, Xiangtao (Frontiers in Plant Science, 2022)
Peony is an excellent ornamental, medicinal and oily plant. Its traditional seed propagation methods have the disadvantages of low propagation coefficient, long seedling cycle, and low seedling emergence rate, which severely restrict the supply of seedlings for the peony industry. Efficient tissue culture technology is an important basis for accelerating its breeding and reproduction, and in vitro seed embryo culturing into seedlings can also effectively avoid the above problems. However, the browning phenomenon caused by man-made damage in the process of seed embryo stripping leads to problems such as low induction rate and difficulty in rooting, and the relationship between anti-browning agents and seed embryo root formation is still unclear. This study intends to improve the induction rate of peony seedlings by using different anti-browning agents and different combinations, and clarify the relationship between anti-browning agents and seedling rooting through transcriptome sequencing methods. The results show that both of the two anti-browning agents AC (activated carbon) and PVP (polyvinyl pyrrolidone) can increase the germination rate of seed embryos. Testing with 0.9g/L AC showed an excellent performance of peony rooting rate and seedling growth, but only AC and the combination of AC and PVP can further promote rooting development. Through transcriptome analysis, we found that AC vs CK (control check); AC vs PVP; PVP vs AC and PVP groups have significantly more differentially expressed genes than AC vs AC and PVP groups. Pathway enrichment analysis shows that " phenylpropanoid biosynthesis "/" cutin, suberine and wax biosynthesis " is significantly enriched in these groups, while AC vs AC and PVP groups are mainly enriched in " cytochrome P450", indicating that AC may promote the further development of roots into seedlings by stimulating " phenylpropanoid biosynthesis " and biosynthesis of stratum cutin and Suberin. This study can lay the foundation for understanding the potential molecular mechanism of the anti-browning agent promoting the rooting of seed embryo seedlings, and also provide a theoretical basis for perfecting the construction of the peony tissue culture and rapid propagation system.